AB0109 Characterisation and comparison of serum biomarkers in patients with rheumatoid arthritis versus osteoarthritis using mass spectrometry. (12th June 2018) - Circiumaru, A.; Butnaru, C.; Bojinca, M.; Petrescu, S.
Abstract : Background: There is increasing interest in biomarkers in medicine, especially for their use as a diagnostic tool and in disease outcome prognosis. Rheumatoid arthritis (RA) is a chronic autoimmune disease with important debilitating outcome potential, therefore a biomarker panel may improve early diagnosis meaning better therapeutic management and lower social costs. Recently, mass spectrometry has emerged as one of the leading methods to identify new biomarkers for different pathologies as well as being able to determine their potential interactors in their cellular pathway. Objectives: To characterise biomarkers using mass spectrometry, from sera of patients with RA and make a comparison between RA, osteoarthritis (OA) and healthy controls. Methods: Blood was collected from 26 subjects, 12 patients with RA, 12 patients with OA, and 2 HC, centrifuged and sera was collected in dedicated tubes. Sera were separated by SDS-Page electrophoresis and stained with Coomassie staining. The samples were subjected to in gel digestion followed by LC/MS analysis. The obtained spectra were searched with Proteome Discoverer v1.4 using SEQUEST algorithm. Results: A total of 985 proteins were identified, from which 323 were specific to the RA study group and 159 were characteristic to the OA group. Prevalent peptides found in the RA group were EGF-containing fibulin-like extracellular matrix protein 2, isoform DeltaLf of lactotransferrin, BPI fold-containing family B member 1 and isoform 2 of BPI fold-containing family A member 1. In the OA study group there was a prevalence in homeobox protein TGIF1, major facilitator superfamily domain-containing protein 9, methyltransferase-like protein 23, a fragment of the salivary acidic proline-rich phosphoprotein, serine/threonine-protein phosphatase 4 regulatory subunit 1, zinc finger protein 229. Conclusions: Our results show a prevalence of peptides linked to cell migration, proliferation and activation in the RA sera as compared to peptides related to cell turnover and tissue senescence observed in OA sera. We believe further mass spectrometry studies of biomarkers in larger cohorts to be a promising tool for diagnosis and outcome prognosis in RA. Disclosure of Interest: None declared